Between the Practice of Religious Ritual and The Journey of Pursuing Cultural Beauty: Menelusuri Motivasi Pengunjung Wisata Religi Den Bach Ma, Hanoi - Dwi Hidayatti (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2020)
People are traveling more these days to attend religious and cultural events. Religious sites clearly attract non-religious tourists in the same way that sacred religious sites attract religious people. Den Bach Ma, a historical temple in the heart of Hanoi, is always crowded with tourists. Foreign tourists from various socio-cultural backgrounds are also adding to the site’s vibrancy. This study focuses on the motivations of tourists who visit Den Bach Ma in Hanoi, as well as an anthropological analysis of tourism. In addition, the researcher employs concepts related to religious tourism. In this study, the qualitative method was used, and the data presented in this study was gathered through observation and interviews with informants. According to the study’s findings, both domestic and foreign tourists engage in a wide range of activities and motivations. As a result of this discovery, the researcher divided the tourists into two groups: (1) religious tourists and (2) secular tourists. However, the researchers discovered that the motivations are extremely complex in reality. It cannot be explained rigidly because, in addition to the previously mentioned categories, there are also categories in which religious tourists’ activities and motivations overlap or mix.